2003
DOI: 10.1080/0968768031000084154
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning of 12 subunits of the V-type ATPase from Mesembryanthemum crystallinum and their expression under stress

Abstract: The vacuolar-type ATPase (V-ATPase) and the vacuolar H(+)-pyrophosphatase are electrogenic proton pumps at plant endomembranes that create the proton motive force required for secondary activated transport and metabolite accumulation during development and adaptation to a variety of adverse growth conditions. Twelve distinct vacuolar H(+)-ATPase (VHA) subunits are suggested to constitute the functional V-ATPase complex. Starting from the available expressed sequence tag (EST) sequences and by homology screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…-ATPase and inorganic pyrophosphatase (H ? -PPase; Garbarino and DuPont 1989;Fukuda et al 1998;Golldack and Dietz 2001;Kluge et al 2003;Vera-Estrella et al 2005). Our results showed that transcripts of HvHVA/68 and HvHVP1 were more abundant in shoots of K305 than shoots of I743 after short-term salt stress (Fig.…”
Section: (C) Hvnhx3mentioning
confidence: 56%
See 1 more Smart Citation
“…-ATPase and inorganic pyrophosphatase (H ? -PPase; Garbarino and DuPont 1989;Fukuda et al 1998;Golldack and Dietz 2001;Kluge et al 2003;Vera-Estrella et al 2005). Our results showed that transcripts of HvHVA/68 and HvHVP1 were more abundant in shoots of K305 than shoots of I743 after short-term salt stress (Fig.…”
Section: (C) Hvnhx3mentioning
confidence: 56%
“…-ATPase and inorganic pyrophosphatase (H ? -PPase; Fukuda et al 1998;Golldack and Dietz 2001;Kluge et al 2003;VeraEstrella et al 2005). Increased Na ?…”
Section: Introductionmentioning
confidence: 96%
“…Various studies have revealed a connection between salt tolerance and a higher activity or expression of the v-ATPase and/or the PPase. Kluge et al (2003) found a transcription induction of v-ATPase-and PPase cDNA by different stress factors such as osmotic stress, heat, cold and salt stress in Mesembryanthemum crystallinum. An enhanced expression of vacuolar Na ?…”
Section: Discussionmentioning
confidence: 98%
“…The influence of salinity stress on membrane protein composition in the tonoplast has long been reported. The levels and activities of tonoplast resident integral membrane proteins such as Na + /H + -antiporters, several subunits of the vacuolar H + -ATPase, Ca 2+ -ATPases and water channels have recently been shown to be affected by salinity stress (Barkla et al, 1994;Dietz and Arbinger, 1996;Tsiantis et al, 1996;Geisler et al, 2000;Kirch et al, 2000;Kluge et al, 2003) and their over-expression may increase the stress tolerance of a plant (Apse et al, 1999). Two fundamental mechanisms required for the maintenance and the regulation of a functional vacuole need to be understood: (1) how is the specific transport of proteins to the vacuole achieved and (b) how is this transport pathway regulated during the plant's adaptation to environmental stress?…”
Section: Introductionmentioning
confidence: 99%